Case Report: Pediatric pontine abscess and ecthyma gangrenosum due to Pseudomonas aeruginosa septicemia - Theros, Jonathan; Wolfe, Madison; Kociolek, Larry; Kolaitis, Irini N. (Frontiers in Pediatrics, 2025)
Brainstem abscesses are remarkably rare, with only a few reports in the pediatric literature. Their presence portends high morbidity and mortality and most commonly present in the setting of immunodeficiency. A 5-year-old boy with a history of recurrent acute otitis media presented to the emergency department with rash, otorrhea, confusion, and fever. He was found to be in septic shock secondary to Pseudomonas aeruginosa bacteremia; a skin exam revealed multifocal ecthyma gangrenosum. He was initially treated with intravenous ceftazidime. Despite adequate antibiotic coverage he had persistent fevers. Whole-body magnetic resonance imaging revealed an expansile pontine mass; dedicated neuroimaging confirmed a 10 mm pontine abscess. Given the lack of neurological deficits on examination, he was treated non-operatively with intravenous cefepime for 9 weeks followed by oral levofloxacin for 30 days and made a nearly complete clinical recovery. Extensive immunodeficiency workup did not identify an immunologic defect. Prompt action through interdisciplinary care meetings and avoidance of early diagnostic closure resulted in an excellent neurological outcome for this patient with this rare case of a P. aeruginosa brainstem abscess.